2014
DOI: 10.1590/s0100-83582014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e nutrição mineral de Sida rhombifolia

Abstract: RESUMO -O experimento foi conduzido com o objetivo de analisar a produção e a distribuição de massa seca e os teores e os acúmulos dos macronutrientes em plantas de guanxuma (Sida rhombifolia) cultivadas em condições padronizadas de nutrição mineral. As plantas cresceram em vasos de sete litros com substrato de areia, que foram irrigados diariamente com solução nutritiva e mantidos em condições de casa de vegetação. Os tratamentos corresponderam às épocas de avaliação (21, 35, 49, 63, 77, 91, 105, 119 e 133 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
3
0
5
Order By: Relevance
“…It is significant that DM yields of this species at 120 days were equal to those of Marandu in the unweeded plots. Sida rhombifolia, despite the low DM accumulation during virtually the entire period, began to show greater vegetative growth only after 90 DAE, which is in agreement with findings of Bianco et al (2014). When analyzing growth and mineral nutrition of S. rhombifolia, these authors found that the species actually has slow vegetative growth up to 80 DAE, with peak DM accumulation occurring after 140 DAE.…”
Section: Coexistence Period (Days) Discussionsupporting
confidence: 81%
“…It is significant that DM yields of this species at 120 days were equal to those of Marandu in the unweeded plots. Sida rhombifolia, despite the low DM accumulation during virtually the entire period, began to show greater vegetative growth only after 90 DAE, which is in agreement with findings of Bianco et al (2014). When analyzing growth and mineral nutrition of S. rhombifolia, these authors found that the species actually has slow vegetative growth up to 80 DAE, with peak DM accumulation occurring after 140 DAE.…”
Section: Coexistence Period (Days) Discussionsupporting
confidence: 81%
“…In most cases, weeds are native species and have greater adaptability to the environment than cultivated plants; this gives plant development adequacy and adjusted allocation capacity of resources from the environment (Erasmo et al, 1997;Bianco et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning S. rhombifolia dry mass accumulation, Bianco et al (2014) reported that N and K are the most required macronutrients; macronutrient accumulation daily rate is cumulative until 94 DAE; and periods of increased accumulation of dry mass and macronutrients occur after 122 DAE.…”
Section: Resultsmentioning
confidence: 99%